The impact of complete dentures on the oral health-related quality of life among the elderly - Yu-Fen Chen; Yi-Hsin Yang; Jen-Hao Chen; Huey-Er Lee; Ying-Chun Lin; John Ebinger; Tsau-Mau Chou (Elsevier, 2012)
Background/purpose: The objective of this study was to assess the relationship between the essential functional qualities of complete dentures and participants' oral health-related well-being among an elderly edentulous population. Materials and methods: Four hundred elderly participants from Taiwan, aged ≥ 65 years, with diverse levels of formal education, received intraoral examinations in accordance with the 10 criteria embedded in the Functional Assessment of Dentures (FAD) and personal interviews in accordance with the Oral Health Impact Profile (OHIP)-14. The mean OHIP-14 scores were compared among categories using a t test or ANOVA. A multiple-regression analysis was used to identify significant FAD criteria related to specific OHIP-14 domains, while adjusting for gender, age, and educational level. Results: Maxillary stability and retention, denture articulation, and occlusion demonstrated significant relationships with the mean OHIP-14 scores and individual mean OHIP-14 domain scores. Maxillary denture stability and denture articulation were the two most significant denture-related variables. Conclusion: A stable and retentive maxillary denture with adequate articulation provided the optimal environment for oral function with the highest level of patient oral health-related well-being in this elderly population.